Laparoscopic Distal Pancreatectomy for Pancreatic Ductal Adenocarcinoma: Time for a Randomized Controlled Trial? Results of an All-inclusive National Observational Study. Issue 5 (November 2015) - Sulpice, Laurent; Farges, Olivier; Goutte, Nathalie; Bendersky, Noelle; Dokmak, Safi; Sauvanet, Alain; Delpero, Jean Robert
Abstract : Objectives: The aim of this study is to compare at a national level, the early and long-term outcome of distal pancreatectomy (DP) performed by laparoscopy (LapDP) or open surgery (OpenDP) for pancreatic ductal adenocarcinoma (PDAC). Background data: LapDP is feasible and safe for benign conditions but its use for PDAC is controversial. Methods: French healthcare databases were screened to identify all patients who had undergone LapDP or OpenDP for PDAC between 2007 and 2012. Endpoints were (i) 90-day mortality, (ii) morbidity, (iii) transfusion rate, (iv) length of hospital stay (LOS), and (v) long-term survival. Logistic regression and adjusted Cox models were used to compare LapDP and OpenDP with regard to these outcomes. Confounders included (i) patients' characteristics; (ii) associated surgical procedures; and (iii) characteristics of the hospital. Performance of the resulting models was determined by the area under the receiver operating characteristic (ROC) curve. Results: Over the 6-year period, there were 2753 operations for PDAC: 2406 OpenDP and 347 LapDP (12.6%). The overall 90-day mortality rate was 5.2%; median LOS was 15 days, and median survival was 38 months. LapDP was not correlated with 90-day mortality but was associated with reduced pleuropulmonary morbidity (odds ratio (OR) 0.73, P = 0.028), blood transfusion (OR 0.44, P = 0.001), and LOS ( P = 0.042), and was associated with increased survival ( P = 0.0007). Conclusions: LapDP has not been adopted widely for PDAC. The early and long-term results of LapDP as currently practiced are as good as those of OpenDP. The next step in the evaluation of LapDP should be a randomized controlled trial (RCT), but such a trial is likely to suffer from insufficient recruitment. Abstract : Supplemental Digital Content is available in the text